Trial design on prophylaxis and treatment of brain metastases: lessons learned from the EORTC Brain Metastases Strategic Meeting 2012 - Preusser, Matthias; Winkler, Frank (European journal of cancer, 2012)
Brain metastases (BM) occur in a significant proportion of cancer patients and are associated with considerable morbidity and poor prognosis. The trial design in BM patients is particularly challenging, as many disease and patient variables, statistical issues, and the selection of appropriate end-points have to be taken into account. During a meeting organised on behalf of the European Organisation for Research and Treatment of Cancer (EORTC), methodological aspects of trial design in BM were discussed. This paper summarises the issues and potential trial strategies discussed during this meeting and may provide some guidance for the design of trials in BM patients.